2013
DOI: 10.1136/bcr-2013-008949
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin and pancytopenia caused by culture-proven delayed onset disseminated bacillus Calmette-Guérin (BCG) infection after intravesical instillation

Abstract: A 78-year-old man was diagnosed with bladder carcinoma in situ and was successfully treated with intravesical bacillus Calmette-Guérin (BCG) instillations. At 6 months after the last dose, he developed fever, weight loss and malaise. He had an extensive negative workup at an outside hospital and was treated empirically with ciprofloxacin for 2 weeks. The fever resolved but returned months later and he was readmitted with pancytopenia, elevated alkaline phosphatase and ground glass opacities on the chest CT. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(16 reference statements)
1
10
0
Order By: Relevance
“… 230 On the other hand, it has been suggested that a positive purified protein derivative (PPD) test before instillation could predict the subsequent occurrence of systemic side effects and, presumably, a better antitumor activity. 15 , 216 Unfortunately, data on previous PPD tests were reported in only 12 cases (4 of them with a positive result 37 , 110 , 136 [and present Case 3]), thus preventing us from drawing any conclusion on this point. However, previous reports do not contain clear recommendations regarding this issue.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 230 On the other hand, it has been suggested that a positive purified protein derivative (PPD) test before instillation could predict the subsequent occurrence of systemic side effects and, presumably, a better antitumor activity. 15 , 216 Unfortunately, data on previous PPD tests were reported in only 12 cases (4 of them with a positive result 37 , 110 , 136 [and present Case 3]), thus preventing us from drawing any conclusion on this point. However, previous reports do not contain clear recommendations regarding this issue.…”
Section: Discussionmentioning
confidence: 72%
“…Chest imaging also play a crucial role in diagnosing disseminated BCG infection and the present review suggests that CT scan should always be preferred over conventional radiography, as the latter technique failed to reveal a miliary pattern in about one-quarter of the patients eventually found to have miliary tuberculosis. 11 , 29 , 37 , 39 , 46 , 63 , 85 , 117 , 141 , 142 , 177 , 214 , 231…”
Section: Discussionmentioning
confidence: 99%
“…The use of intravescial BCG has been reported to be associated with systemic autoimmune diseases, such as cyroglobulinemia vasculitis [ 17 ], autoimmune retinopathy [ 18 ], Henoch-Schonlein purpura [ 19 ], and haemophagocytic syndrome [ 20 ]. BCG has also caused a pancytopenia due to bone marrow infection, which may be delayed up to two years post-treatment [ 4 , 20 ]. This highlights that intravesical BCG may produce systemic side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…BCG is a live attenuated strain of Mycobacterium bovis , and although minor side effects are common, serious side effects occur in less than 5% of patients, of which most are local and present early after treatment [ 2 ]. Systemic side effects have included infection, autoimmune disorders, and pancytopenia [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Rarer is the identification of M. bovis as the causative agent of these disseminated infections, feasible only with molecular techniques. [10] Here we present seven cases of pneumonitis after intravesical BCG therapy and the identification of M. bovis in two of these cases.…”
mentioning
confidence: 99%